Draft Annual Plan 2006-2007 Volume-I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 2006)
Rajasthan, with a total geographical area of 3,42,239 Sq. km., is the largest State in the country. Administratively, Rajasthan is divided today into 7 divisions and 32 districts, which are further sub-divided into 188 sub-divisions, 241 tehsils and 237 development blocks. 1.2 the population of Rajasthan, standing at 5.65 crore (2001 Census) and a density of 165 persons per sq. km., recorded a decadal growth rate of 28.41 percent over the population of 4.40 crores (1991 Census) and a density of 129 persons per sq. km. the SC population in the State stood at 17.2% of the total and that of ST at 12.6%.
Government of Rajasthan Planning Department